Effect of Process Parameters on Extraction of Essential Oil from Cumin - Sangani, V P; Patel, N C (Journal of Agricultural Engineering, 2013)
Cumin is an important spice containing about 2.5 to 4 % essential oil. The effect of particle sizes of cumin on distillation time was studied using a completely randomized design. Six levels of particle size, i. e. whole cumin (2.33 mm), 1000 µm, 711 µm, 503 µm, 356 µm, 251 µm of cumin were studied. Particle size of 356 µm and 5 h of distillation time is recommended for higher recovery and good quality of essential oil.